Study on a new fault phase selector in interconnection line with wind turbine based on doubly-fed induction generator's wind farm. (October 2022) - Xiao, Fan; Liu, Dan; Ji, Xiaotong; Cao, Kan; Xiong, Ping
Abstract: The fault current characteristics of wind turbine based on doubly fed induction generator (DFIGWT) is complicated. The conventional superimposed phase selectors cannot meet the requirements of phase selection in the interconnection line based on DFIGWT's wind farm. In this paper, according to the low voltage ride-through strategy of DFIGWTs, the shortcomings of traditional superimposed phase selector are analyzed. Then, a new fault phase selector is proposed based on the amplitude ratio between superimposed phase voltage and superimposed phase-to-phase voltage. According to the proportional relationship between the superimposed phase voltage and superimposed phase-to-phase voltage in the interconnection line with DFIGWT-based wind farm, the fault phase selection coefficients are proposed. Based on the proposed fault phase selection coefficients, the fault phases under different fault conditions can be identified. Finally, the effectiveness and reliability of the proposed fault phase selector are validated by simulation. Test results show that the proposed method is not affected by the LVRT control strategies and can meet the phase selection requirements of new energy sources under different LVRT strategies conditions.